2017
DOI: 10.1007/s40262-017-0569-6
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacokinetics of Fentanyl and Its Derivatives in Children: A Comprehensive Review

Abstract: Fentanyl and its derivatives sufentanil, alfentanil, and remifentanil are potent opioids. A comprehensive review of the use of fentanyl and its derivatives in the pediatric population was performed using the National Library of Medicine PubMed. Studies were included if they contained original pharmacokinetic parameters or models using established routes of administration in patients younger than 18 years of age. Of 372 retrieved articles, 44 eligible pharmacokinetic studies contained data of 821 patients young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 188 publications
3
60
0
1
Order By: Relevance
“…The doses were generally very high in the included studies. The authors concluded that preterm and term infants showed lower clearance and protein binding, but that much larger studies must be made to get reliable data .…”
Section: Discussionsupporting
confidence: 72%
“…The doses were generally very high in the included studies. The authors concluded that preterm and term infants showed lower clearance and protein binding, but that much larger studies must be made to get reliable data .…”
Section: Discussionsupporting
confidence: 72%
“…A recent study [6] indicated that a sigmoidal E max model can be used to describe the body weight versus clearance data across the observations. This study evaluated the predictive performance of a sigmoidal E max model for ten drugs.…”
Section: Model 2: Body Weight-dependent Sigmoidal E Max Modelmentioning
confidence: 99%
“…1 Their adverse effects are related to dose, which include respiratory depression, sedation, nausea, vomiting, constipation, pruritus, physical dependence, the risk of addiction, bradycardia, and skeletal muscle rigidity. 2,3 Immediately after their introduction into the market as drugs for the treatment of pain, there was a significant increase in abuse, off-label and illicit uses. [4][5][6] Besides a series of illicit fentanyls (Fig.…”
Section: Introductionmentioning
confidence: 99%